Spatiotemporal change of water use efficiency on different ecological restoration areas of Gansu, China - Zhang, Xiujuan; Wang, Jiangang; Zhou, Yue; Ma, Quanlin; Wang, Xinyou (Frontiers in Ecology and Evolution, 2025)
Water use efficiency (WUE) is an important indicator to characterize the carbon and water cycle of ecosystems. Using the Google Earth Engine platform, MODIS data were used to calculate WUE. Trend analysis, R/S analysis, partial correlation analysis, PLS-SEM, and other methods were used to analyze the spatiotemporal dynamics of WUE in Gansu province from 2001 to 2020, and to explore the impact of environmental factors on WUE. The results show that: (1) The annual average WUE in Gansu from 2001 to 2020 was 1.71 gCm−2mm−1, and the WUE showed an upward trend. (2) WUE is high in the southeast and low in the northwest, and the WUE in 77.5% of regions is in a state of continuous and stable change. (3) In 76.5% of the regions in Gansu, WUE was positively correlated with lagged SPEI, and the areas with a lag of 6 to 12 months accounted for 47.36%. (4) The total effect of vegetation factors is positive. The impact of climate on WUE through vegetation is 0.685 in Gansu. This study is of great significance for gaining a deeper understanding of the response mechanism of regional water cycle to climate change under the dual background of vegetation restoration and environment in Gansu, and for accurate assessment and optimization of regional water resources management.